Seating Arrangements in Discussion Groups as the Factor of the Students' Willingness to Speak English in Foreign Language Classroom - Ella Ismi Anggriani; Isna Humaera (AL LUGHAWIYAAT, 2021)
This research reports the extent to which the teacher factor causes the willingness of students to speak in a foreign language class. Looking at the majority of students who do not speak when in a foreign language class, this study is therefore conducted to see in terms of which teacher factors can make students want to talk. This research uses a qualitative approach with student reflection documents. The researcher selected 25 students as participants in this study. This research was conducted by observation and taking data through filling reflections conducted by students through Google Form. From the results of the reflection analysis the researcher found that each student had the same opinion in expressing their way to want to talk in class, that is by looking at or depending on what method the teacher used in the classroom. In this case, the method used by the teacher in the classroom is the method of seating arrangements in discussion groups. Then this is the teacher’s factor that causes the willingness of students to speak in a foreign language class.Keywords: Teachers’ Factor; Willingness to Communicate (WTC)